Prediction of live birth - selection of embryos using morphokinetic parameters - Tvrdonova, Katerina; Belaskova, Silvie; Rumpikova, Tatana; Rumpik, David; Myslivcova Fucikova, Alena; Malir, Frantisek (Biomedical papers, 2024)
Backround. The goal of assisted reproduction is for a couple treated with IVF techniques to end the treatment by giving birth to a healthy baby. A neccessary presumption for success is the identification of the best embryo with high implantation and developmental potential. One option is to select an euploid embryo by invasive preimplantaion genetic testing for aneuploidy (PGT-A) or it is possible to select the best embryo by non-invasive time-lapse monitoring (TLM), specifically based on morphokinetic parameters and morphological markers that are able to identify an embryo with high developmental potential. Materials and Methods. The study involved a total of 1060 embryos (585 euploid and 475 aneuploid embryos after PGT-A) with good morphology from 329 patients in the period 01/2016-10/2021. All embryos were cultured in a time-lapse incubator, trophectoderm (TE) cells biopsies for PGT-A examination were performed on day 5 (D5) or day 6 (D6) of culture. During the study period, 225 frozen embryo transfers (FET) of one euploid embryo were performed. Based on the treatment outcome, the embryos were divided into 2 groups - euploid embryos, which led to the birth of a healthy child, and euploid embryos that did not show fetal heartbeat (FHB) after FET. Results. Based on the statistical analysis of the embryos without implantation and the embryos with live birth, it is clear that the morphokinetic parameters t5 (time of division into 5 cells) and tSB (time of start of blastulation) are significantly different. Conclusion. The results suggest that of the morphokinetic parameters tSB and t5 are predictive indicators for selecting an embryo with high developmental potential and with a high probability of achieving the birth of a healthy child.
Keywords: embryo; time-lapse; morphokinetics; implantation; live birth